Repertoire Development and the Control of Cytotoxic/Effector Function in Human γδ T Cells - Elizabeth M. Urban; Andrei I. Chapoval; C. David Pauza (Clinical and Developmental Immunology)
T cells develop into two major populations distinguished by their T cell receptor (TCR) chains. Cells with the αβ TCR generally express CD4 or CD8 lineage markers and mostly fall into helper or cytotoxic/effector subsets. Cells expressing the alternate γδ TCR in humans generally do not express lineage markers, do not require MHC for antigen presentation, and recognize nonpeptidic antigens. We are interested in the dominant Vγ2Vδ2+ T cell subset in human peripheral blood and the control of effector function in this population. We review the literature on γδ T cell generation and repertoire selection, along with recent work on CD56 expression and defining a cytotoxic/effector lineage within the phosphoantigen-reactive Vγ2Vδ2 cells. A unique mechanism for MHC-independent repertoire selection is linked to the control of effector function that is vital to the role for γδ T cells in tumor surveillance. Better understanding of these mechanisms will improve our ability to exploit this population for tumor immunotherapy.